Upaya Pemerintah Kota Banda Aceh dalam Melindungi Anak Penyandang Disabilitas (Banda Aceh City Government's Efforts to Protect Children with Disabilities) - Rispalman, Rispalman; Islami, Iman (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2019)
Children with disabilities are vulnerable to poor treatment and the growth will be very difficult in a community environment. Therefore, it must be a child with a disability given the attention of the local government to provide protection for the child's disability. This research is categorized as field research Research) and Library Research, is a type of qualitative research. The results of this research show, based on data obtained from the social service city of Banda Aceh, currently the city of Banda Aceh there are 467 children with disabilities with the category of 7 types of disabilities, of the 7 types of disability that most of the levels are Tuna Runggu and Tuna. In the management of children with disabilities, the Government of Banda Aceh carried out several activities in terms of social assistance fund Rp. 4 million (four million rupiahs) per year, the establishment of a disabled child Family Communication Forum (FKKADK) and the provision of disability aids for children with disabilities according to their degree of disability. The efforts of the activities undertaken by the Government of Banda Aceh are in accordance with the provisions of article 8 of the Candy PPPA number 4 year 2017 about special protection for children with disabilities who said that the implementation of special protection for children with disabilities in the form of activities to be a reference for the area in drafting the action plan is adjusted to the condition, the situation, needs, and capabilities of the area and with the appropriate implementation on the article with article 90 of law number 8 year 2016 social rehabilitation, social protection, social empowerment, and social security. In the implementation of child protection with disabilities in Banda Aceh in accordance with the provisions of Islamic law relating to maqasid sharia.